PEMENUHAN HAK-HAK PENDIDIKAN BAGI KELOMPOK DISABILITAS DI KABUPATEN SUMENEP (STUDI IMPLEMENTASI PERATURAN BUPATI NOMOR 13 TAHUN 2024 PADA JENJANG PENDIDIKAN DASAR, MENENGAH, DAN PENDIDIKAN TINGGI) - Nurul Hidayatullah, Moh; Syafi'i, Imam; Ikmal, Moh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is a fundamental right for all citizens, including persons with disabilities. The Sumenep Regency Government has enacted Regent Regulation Number 13 of 2024 as a legal basis for fulfilling inclusive education rights across all educational levels. This study aims to analyze the implementation of this regulation using a descriptive qualitative approach through interviews and observations. The results indicate that the policy has begun to be implemented through the application of non-discrimination principles, but it has not yet been fully effective due to limitations in infrastructure, educator readiness, and institutional support, particularly at the higher education level. Therefore, strengthening technical policies, enhancing educator capacity, and providing disability-friendly facilities are necessary to realize sustainable inclusive education in Sumenep Regency.